The effect of final irrigation solution and irrigation techniques on the flexural strength and elastic modulus of root canal dentin: an experimental study - yuniva, Hasna syifa; Ratih, Diatri Nari; Widyastuti, Andina (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2026)
Introduction: Root canal irrigation facilitates debris removal, lubrication, and the dissolution of organic and inorganic tissues while preventing smear layer formation. However, the chelating properties of final irrigants may deplete calcium ions from the dentin, potentially compromising the flexural strength and modulus of elasticity of the root canal walls. This study aims to analyze the effects of various final irrigants and agitation techniques on these mechanical properties of radicular dentin. Methods: Forty-five mandibular premolars were prepared and randomly divided into three groups (n=15). Group 1 was irrigated with 17% EDTA, Group 2 with 0.2% chitosan nanoparticles, and Group 3 with Ultra Clean. Each group was further subdivided into three subgroups (n=5) based on the agitation technique used: manual (A), sonic (B), and ultrasonic (C). Flexural strength and elastic modulus were measured using a Universal Testing Machine (UTM). Results: Two-way ANOVA showed that the type of irrigating solution, agitation technique, and their interaction significantly affected flexural strength and elastic modulus (p<0.05). Post-hoc LSD analysis revealed significant differences among groups for both flexural strength and elastic modulus (p<0.05), with several exceptions in specific comparisons within the EDTA and Ultra Clean groups, as well as between Ultra Clean manual agitation subgroup and the 0.2% chitosan nanoparticle subgroup (p>0.05). Conclusion: The highest flexural strength and elastic modulus values were observed in the group treated with 0.2% chitosan nanoparticles combined with sonic agitation, while the lowest values were found in the 17% EDTA group using manual agitation.Efek jenis bahan irigasi akhir dan teknik irigasi terhadap kekuatan fleksural dan modulus elastisitas dentin saluran akar: studi eksperimental in vitroPendahuluan: Irigasi saluran akar berfungsi membersihkan debris, melumasi saluran, melarutkan jaringan organik dan anorganik, serta mencegah terbentuknya smear layer. Namun, sifat khelasi pada bahan irigasi akhir berpotensi mengikis dinding saluran akar dengan mengikat ion kalsium, yang dapat memengaruhi kekuatan fleksural dan modulus elastisitas dentin. Penelitian ini bertujuan untuk menganalisis pengaruh jenis bahan irigasi akhir dan teknik agitasi terhadap sifat mekanis dentin saluran akar akar. Metode: Empat puluh lima premolar mandibula di preparasi, dibagi menjadi tiga kelompok secara acak masing-masing kelompok terdiri dari 15 sampel. Kelompok 1 di irigasi dengan EDTA, kelompok 2 diirigasi dengan kitosan nanopartikel 0,2% dan kelompok 3 di irigasi dengan Ultra clean. Masing-masing kelompok dibagi lagi menjadi 3 kelompok dan setiap kelompok terdiri 5 sampel. Kelompok A digitasi manual, kelompok B sonik, dan kelompok C ultrasonik. Setelah itu dilakukan uji =kekuatan fleksural dan modulus elastisitas dengan Universal Testing Machine (UTM). Hasil: Uji ANAVA Bahan irigasi akhir, teknik irigasi, dan interaksi keduanya berpengaruh signifikan terhadap kekuatan fleksural dan modulus elastisitas (p<0,05). Hasil Post-Hoc LSD menunjukkan perbedaan signifikan antarkelompok untuk kekuatan fleksural dan modulus elastisitas dentin (p<0,05), dengan beberapa pengecualian pada perbandingan metode tertentu dalam kelompok EDTA 17% dan Ultra Clean, serta antara Ultra Clean manual dan kitosan nanopartikel 0,2% (p>0,05). Simpulan: Nilai kekuatan fleksural dan modulus elastisitas tertinggi pada penggunaan kitosan nanopartikel 0,2% dengan teknik agitasi sonik serta terendah pada penggunaan EDTA 17% dengan teknik agitasi manual.